Educação profissional e tecnológica: a contribuição do Instituto Federal do Rio Grande do Sul no desenvolvimento de Viamão (RS) - Vidor, Alexandre Martins (Universidade do Vale do Rio dos Sinos, 2015)
The aim of the study was to analyze the perception and expectation of the IFRS contribution, through professional and technological education in the territorial development of the municipality of Viamão (RS). The methodology used was a documentary and bibliographical analysis, complemented with semi-structured interviews with institutional managers of IFs, local social actors and graduates of technical courses offered by the campus Viamão. It was possible to show through the results that the IFs are responsible for providing EPT at all levels and types of education, training and they are qualifying citizens with a view to professional practice. The orientation of its training offer should be in line with the vocation and local potential in order to promote socio-economic development of the territory. In addition, it was found through common perception of respondents that the IF is an agent of territorial development, although there were different dimensions of understanding. In spite of having great expectations about the IF's contribution to the development of Viamão we found the need for greater interaction between the actors operating in the territory, expanding the understanding of the institutional functions of each. Finally, the regulatory and institutional framework, analyzed with the results of interviews with the perception of a representative set of actors involved in territorial dynamics, showed expectations and IFRS contributions of possibilities for the socioeconomic development of Viamão, in order to overcome inequalities and promote territorial development.
Keywords: Educação profissional e tecnológica; Institutos Federais; Desenvolvimento territorial; Professional education and technology; Federal Institutes; Territorial development; ACCNPQ::Ciências Sociais Aplicadas::Economia